Pengaruh Perbaikan Rolling Resistance Pada Jalan Angkut Terhadap Produktivitas Alat Muat Dengan Menggunakan Aplikasi TALPAC 10.2 di PT. lotus SG Lestari - Putra Desandra Wicaksana; A Silvan Erusani; Milawarma Milawarma (Syarif Hidayatullah State Islamic University, 2021)
Productivity is an important thing in doing mining business, there are many parameters that affect such as the use of the equipment used, the condition of the operator at work, the condition of the front of the mining area, and also the haul roads used to transport the mining products which have a strong influence on productivity. This research will examine the effect of the haul road on productivity, the haul road itself has many parameters such as grade, crossslope, rolling resistance, and the material used for road construction. This research only focuses on improving rolling resistance. This research was conducted with the aim of knowing the effect of rolling resistance improvement on the productivity of the loading device. This research was conducted using the TALPAC 10.2 application. The tools used in this study were the Komatsu PC-400 loading tool and the Komatsu HD 325-5 for transportation. From the results of the TALPAC calculation, it is expected that there will be an increase in productivity and it can be seen that after the road is repaired the productivity of the Komatsu PC-400 increases from 90.96 bcm / hour to 96.89 bcm / hour. Keywords : Rolling Resistnace, Productivity, TALPAC